2016
DOI: 10.2169/internalmedicine.55.5820
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Endoscopic Gallbladder Stenting for Acute Cholecystitis in Patients with Concomitant Unresectable Cancer

Abstract: Objective Endoscopic gallbladder stenting (EGBS) is an alternative treatment option for high-risk surgical patients with acute cholecystitis. However, there are no reports focusing on EGBS in patients with concomitant unresectable cancer. The aim of this study was thus to evaluate EGBS in such patients. Methods Twenty-two consecutive patients with acute cholecystitis and unresectable cancer were enrolled between September 2010 and December 2014. Their median age was 74.5 years (range: 51-95). Thirteen patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…The complications typically associated with ETGBD are post-ERCP pancreatitis, perforation of the cystic duct, and cholangitis. The rate of complications is reported to be 0 % to 16 % 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 , which is similar to our results. Two patients developed mild pancreatitis after ETGBD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The complications typically associated with ETGBD are post-ERCP pancreatitis, perforation of the cystic duct, and cholangitis. The rate of complications is reported to be 0 % to 16 % 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 , which is similar to our results. Two patients developed mild pancreatitis after ETGBD.…”
Section: Discussionsupporting
confidence: 92%
“…There were no significant differences between ETGBD and PTGBD with respect to decrease in WBC count and serum CRP levels after gallbladder drainage. Reportedly, ETGBD is a practical and effective alternative to PTGBD 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 . However, it has not been established as a standard treatment owing to technical difficulty 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, spontaneous drainage through EGBS does carry the risk of stent occlusion as a result of the high viscosity of the drained biliary contents, with previous research reporting EGBS placement after cholecystitis resolution with external drainage. 15,16 Our gallbladder drainage procedure is unique in this way, providing both gallbladder irrigation and stenting during the same endoscopic intervention, thereby providing the combined benefits of both internal and external drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of the procedure was 100% (5 of 5) and was higher than that of emergent ETGS (77.5%, 31 of 40). Hatanaka et al reported on 2 patients with unresectable cancer who had undergone PC because of failed ETGS, and then underwent a successful ETGS with a rendezvous approach [8]. During the rendezvous procedure, a PC-placed guidewire was grasped at the tip of the duodenoscope; then, the duodenoscope and wire were withdrawn.…”
Section: Discussionmentioning
confidence: 99%